Semiconductor Optics - Klingshirn, Claus F. (Advanced Texts in Physics, 2005)
The book on Semiconductor Optics has been favourably received by the s- dents and the scienti?c community worldwide. After the ?rst edition, which appeared in 1995 several reprints became necessary starting from 1997, one of them for the Chinese market. They contained only rather limited updates of the material and corrections. In the meantime scienti?c progress brought a lot of new results, which necessitate a new, seriously revised edition. This progress includes bulk se- conductors, but especially structures of reduced dimensionality. These new trends and results are partly included in existing chapters e. g. for phonons or for time-resolved spectroscopy, partly new chapters have been introduced like the ones on cavity polaritons and photonic structures. We based the description of the optical properties againon the simple and intuitively clear model ofthe Lorentz-oscillatorsandthe concept of polaritons asthequantaoflightinmatter. Butsincethereispresentlyatrendtodescribe at least the optical properties of the electronic system of semiconductors by the optical or the semiconductor Bloch equations, a chapter has been added on this topic written by Prof. Dr. R. v. Baltz (Karlsruhe) to familiarize the reader with this concept, too, which needs a bit more quantum mechanics compared the approach used here. The chapter on group theory has been revised by Prof. Dr. K. Hummer ¨ (Karlsruhe/Forchheim) Karlsruhe, C. F. Klingshirn September 2004 Preface to the First Edition One of the most prominent senses of many animals and, of course, of human beingsissightorvision.